Seeding phenology influences wood mouse seed choices: the overlooked role of timing in the foraging decisions by seed-dispersing rodents - Sunyer, Pau; Espelta, Josep Maria; Bonal, Raul; Muñoz, Alberto (Behavioral Ecology and Sociobiology, 2014)
Scatter-hoarding rodents influence the population dynamics of plants by acting as seed predators and dispersers. Therefore, rodent foraging preferences for certain seed traits (species, size, condition) have been extensively studied. However, to what extent these preferences are fixed or they track the temporal changes on seed characteristics due to phenological differences has been seldom explored.We stud- ied the temporal variability in seed preferences by wood mouse (Apodemus sylvaticus), according to phenological changes in seed characteristics of two co-occurring oaks (Quercus ilex and Quercus pubescens). The phenology of acorn abundance and the acorn predation/dispersal patterns by rodents were monitored over an entire seeding season. Results revealed temporal changes in rodent preferences for acorns of the two oaks, matching their different seeding phe- nology (earlier in Q. pubescens and later in Q. ilex). On the other hand, whatever the species considered, rodents preferred larger and sound acorns along the entire season, although the dispersal of infested ones increased slightly during the peaks of acorn drop. The observed influence of seeding phenology on seed choices by rodents warns about inferring definite conclusions regarding their foraging behavior when arising from short-term experiments. Indeed, this study reveals that foraging preferences may be highly dynamic and context- dependent for some seed traits (e.g., species and condition), rather than fixed behavioral patterns. Plasticity in rodent for- aging choices may allowthem to successfully exploit different oaks with uncoupled seeding phenologies, while potentially favoring their coexistence.
Keywords: acorn; Apodemus sylvaticus; dispersal; Quercus; seed; seed traits

Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation

Acorn crop size and pre-dispersal predation determine inter-specific differences in the recruitment of co-occurring oaks. - Espelta, Josep Maria; Cortes, P.; Molowny-Horas, R.; Retana, J. (Oecologia, 2009)
The contribution of pre-dispersal seed predation to inter-specific differences in recruitment remains elusive. In species with no resistance mechanisms, differences in pre-dispersal predation may arise from differences in seed abundance (plant satiation) or in the ability of seeds to survive insect infestation (seed satiation). This study aimed to analyse the impact of pre-dispersal acorn predation by weevils in two co-occurring Mediterranean oaks (Quercus ilex and Quercus humilis) and to compare its relevance with other processes involved in recruitment. We monitored the patterns of acorn production and acorn infestation by weevils and we conducted experimental tests of acorn germination after weevil infestation, post-dispersal predation and seedling establishment in mixed forests. Monitoring and experimental data were integrated in a simulation model to test for the effects of pre-dispersal predation in recruitment. In both oaks pre-dispersal acorn infestation decreased with increasing acorn crop size (plant satiation). This benefited Q. ilex which exhibited stronger masting behaviour than Q. humilis, with almost a single and outstanding reproductive event in 6 years. Acorn infestation was more than twice as high in Q. humilis (47.0%) as in Q. ilex (20.0%) irrespective of the number of seeds produced by each species. Although germination of infested acorns (seed satiation) was higher in Q. humilis (60%) than in Q. ilex (21%), this could barely mitigate the higher infestation rate in the former species, to reduce seed loss. Conversely to pre-dispersal predation, no inter-specific differences were observed either in post-dispersal predation or seedling establishment. Our results indicate that pre-dispersal predation may contribute to differences in seed supply, and ultimately in recruitment, between co-existing oaks. Moreover, they suggest that seed satiation can barely offset differences in seed infestation rates. This serves as a warning against overemphasising seed satiation as a mechanism to overcome seed predation by insects.
The following values have no corresponding Zotero field: accession-num: 19544074
Keywords: Animals; Feeding Behavior; Feeding Behavior: physiology; germination; Germination: physiology; Models, Biological; Quercus; Quercus: physiology; Seeds; Seeds: growth & development; Spain; Species Specificity; weevils; Weevils: physiology

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival